Specific language impairment in Croatian - pattern of errors - Ivšac, Jasmina (Array, 2004)
Up to date there has been a lot of scientific attention directed to the phenomenon of specific language impairment (SLI) in preschoolers. It is well documented that SLI stands for a heterogeneous category which incorporates between 5% and 7% of the population (Tomblin et al., 1998.). SLI covers difficulties in a range of language areas on some and/or many levels. There are many theories and debates concerning etiology, possible subclassifications and methodology of investigation. The majority of studies (and therefore data and results) is done on English language. Descriptions of each level of language structure enabled cross-linguistic studies and comparison, therefore getting some mutual correlates. In Croatian, as a highly inflected language, morphology plays an important role in words of some word classes, especially those carrying the most important semantic information. This strong morphological encoding gives the speakers of Croatian relative freedom in choosing the word order, enabling them to use the word order in emphasizing particular elements in the sentence. Croatian language does not have a long history in studying SLI. The profiles of SLI children have been described in some segments, but the relative poorness of the existing data on regular language development makes it difficult to give the precise description of SLI. The morphological component of the language is the one that is most affected by the SLI. Seven cases and two numbers of the noun and adjective declension and three persons, two numbers and six tenses of the verb conjugation represent the biggest challenges for the Croatian children with the SLI. If the morphology does not function, the syntax does not necessarily provide the additional redundant grammatical information. Eight well documented subjects which all meet the criteria for SLI diagnosis were followed during the one year period. The study was designed with guiding principle for possible classification of errors, but at the same time with awareness that the sample is too small to generalize. The subjects' conversations and narrative episodes were recorded. The episodes were transcribed and analyzed to get insight in the frequency and type of errors these children make.